Broadcasting Service Quality in Increasing National TVRI Audience Satisfaction - Hakim, Arief Rahman; Nenobais, Harry; Damasinta, Alfiana (Journal of Government Science Studies, 2025)
: Currently, technology is increasingly sophisticated with the development of the era of globalization. The development of the modern era, makes today's society follow the increasingly developing modernization, competition between televisions presents interesting programs. Likewise, TVRI as a Public Broadcasting Institution has problems that must be resolved immediately, starting from human resources, programs, and broadcasting facilities and infrastructure. Based on this background, researchers are interested in conducting a study entitled "Broadcasting Service Quality in Increasing the Satisfaction of National TVRI Viewers". Researchers chose the title intending to know the quality of National TVRI broadcasting services in increasing viewer satisfaction and know the dimensions of service quality. This study uses the theory of Service Quality, namely services that satisfy the community by service standards and principles of public service or viewers. The dimensions of Service Quality are Tangible, Reliability, Responsiveness, Assurance, and Empathy. This study uses the post-positivism paradigm through a qualitative descriptive approach and uses interview and observation methods to collect the required data. Based on the research results, it was concluded that in terms of broadcasting services, it is necessary to pay attention again, as they are still not by the expectations or needs of the audience, and suggestions are made for TVRI broadcasting services to improve the provision of education to high-achieving employees for development.